Methodological Characteristics of Clinical Trials: Impact of Mandatory Trial Registration - Ashish Kumar Kakkar; Biswa Mohan Padhy; Sudhir Chandra Sarangi; Yogendra Kumar Gupta (Frontiers Media S.A., 2019)
Purpose: Numerous studies across multiple specialties have evaluated the impact of trial registration on quality of study reports and found significant improvements over several domains. However, the impact of mandatory trial registration on the quality of clinical trial protocols remains hitherto unexplored. Methods: We carried out a retrospective cohort study of clinical trial applications submitted to drug regulatory authority of India for initial review with the objective of comparing methodological characteristics of their protocols. Since trial registration was made mandatory in the country in June 2009, we selected two study periods as between January 2007 to May 2009 (Period I) and July 2009 to December 2011 (Period II). Seventy-five protocols were randomly selected using a computer-generated list for each study period, making a total of 150 protocols. Data on twelve key methodological characteristics were collected including clearly defined primary outcomes, randomization, blinding, use of control group, statistical methods, handling of withdrawals amongst others. Results: More than 3/4th of the trial applications in the two study periods were for new chemical entities and nearly 90% were pharmaceutical industry sponsored studies. Comparing the period before and after implementation of mandatory trial registration, description of clearly defined trial outcomes improved from nearly 42% to 80% (p<0.001), sample size justifications increased from 38% to 70% (p<0.001) and use of allocation concealment improved from 24% to 49% (p=0.001). Marked improvement was also noted for blinding, description of statistical methods and handling of withdrawals and dropouts. Remaining characteristics did not change significantly between the two study periods. The mean cumulative scores for the study protocols improved significantly from 7± 0.296 in the first period to 8.93± 0.346 (p<0.001) in the second period. Conclusions: Our study found a significant improvement in the methodological quality characteristics of the protocols particularly in elements related to minimization of bias and statistical methods, which could be attributed to mandatory trial registration. Overall, the significant improvement was limited to global clinical trials, and room for improvement was noted for two quality characteristics - proportion of randomized studies and trials adequately describing the generation of allocation sequence.